Drivers and barriers for commercial FTTH wholesale of alternative competitors - a case study-oriented analysis - Sebastian Tenbrock; Christian Wernick (International Telecommunications Society (ITS), 2021)
In Europe, alternative network operators have rolled out own FTTH networks in numerous regions. They often realise first mover advantages and thus dispose (at least for some time) of superior infrastructures. In comparison to copper infrastructures of incumbent operators, most alternative networks are not subject to access regulation (as long as they are not subsidised by state-aid programs or the network operator is deemed as SMP operator). Against this backdrop, the decision to offer wholesale products to third parties represents a business decision depending on various factors. The objective of this paper is to investigate the state of development of the market for alternative FTTH wholesale services in five European countries (Austria, Denmark, Germany, Sweden, and Switzerland). It aims to identify drivers and barriers and to identify common patterns in the countries under observation. Furthermore, we give some recommendations on policy measures which might help to remove existing barriers and further wholesale on alternative networks. We apply a case study approach, which builds on primary and secondary research including interviews with market experts from business and policy.
Keywords: 330